Hepatitis B vaccination status and associated factors among students of medicine and health sciences in Wolkite University, Southwest Ethiopia: A cross-sectional study. - Kassahun Haile; Abebe Timerga; Ayenew Mose; Zebene Mekonnen (PLoS ONE)
Background Hepatitis B virus (HBV) infection is a significant global public health problem. Health care providers and medical students in developing countries including Ethiopia are at an increased risk of contracting HBV due to the high burden of this infection. The most effective way of prevention against HBV infection is vaccination of health care providers. However, there is a paucity of data on the HBV vaccination coverage among students of health science in Ethiopia. Therefore, this study aimed to determine HBV vaccination coverage and associated factors, level of knowledge, attitudes, and practices (KAP) towards HBV among students of medicine and health science at Wolkite University. Materials and methods A cross-sectional study was conducted at Wolkite University among 417 study participants from November to December 2020. The study participants were recruited by using a simple random sampling technique. Data were collected using a self-administered structured questionnaire and analyzed using SPSS version 21. A binary logistic regression model was used to determine the factors associated with full-dose vaccination status. Statistical significance was set at P-value <0.05. Results Out of the 417 study participants, 5.8% (95%CI: 3.8-7.9) received a full-dose of the HBV vaccine in this study. Unavailability and high cost of the vaccine were frequently mentioned reasons for not being vaccinated against HBV. About 73.6%, 36.2%, and 47% of participants had good knowledge, positive attitudes, and good practices towards HBV, respectively. Being male gender (AOR: 8.8; 95%CI: 2.9-27), rural residence (AOR: 3.6; 95%CI:1.2-10.6), positive attitude (AOR: 0.44; 95%CI: 0.1-1.1), good practice (AOR: 0.17; 95%CI: 0.05-0.5), medicine department (AOR: 5.9; 95%CI: 1.2-29), being second-year student (AOR: 11.7; 95%CI: 2.7-50.9), third-year student (AOR: 19; 95%CI: 4.25-45), and fourth-year student (AOR: 27; 95%CI: 5.8-56) were significantly associated factors with full-dose vaccination status. Conclusion Our study revealed that only small proportions (5.8%) of study participants received full-dose HBV vaccination. Vaccinations of students before starting clinical attachments, provisions of training for students on infection prevention mechanism and universal precautions particularly on HBV, increasing the uptake of the HBV vaccine, creating awareness on attitude and practice of students towards HBV to enhance uptake of the vaccine are recommended.